On the knowledge field of administration: management, organizations and division of labor (Management and Connections Journal, 2022)
In this theoretical and didactic essay, the aims are to show and discuss a graphical model for the management and organizational studies field of knowledge. We analyze the scope, limits, and relations between management and organizational studies (OS). In the end, we present a visual model of representation that integrates management and organizations as the main objects of the field. The method employed was the integrative systematization of references and logical deduction. The thesis of the paper is that the typical objects of the management/OS field—management practices and organizations—are respectively phenomenal manifestations of the technical and social divisions of labor in the capitalist mode of production. Therefore, the interests of the field would be within the scope of the dialectical and dialogical relations between theses social processes.
Keywords: Management; Organizational Studies; Organizations; Dialectical and Historical Materialism